STRATEGI PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL ACCELERATED LEARNING - Mustika, Aulia Musla (Lentera: Jurnal Ilmiah Kependidikan, 2014)
Learning aims to improve students competencies. Learning objectives will be achieved if students understand the material being studied optimally. Therefore, appropriate learning models necessary to achieve these goals, particularly in mathematics. The learning model is selected learning model that can make students feel comfortable in the learning of mathematics, and the learning model chosen is Accelerated Learning. Accelerated Learning has five stages of learning, namely: 1) motivate the mind, 2) obtain information, 3) investigate the meaning, 4) triggers a memory, 5) show off what you have mastered, and 6) reflect on how you learn. Paper presented to the literature method to discuss how the theoretical description of the model of Accelerated Learning and how the learning strategy by using a mathematical model of Accelerated Learning.